Dehydroepiandrosterone Biosynthesis, Role, and Mechanism of Action in the Developing Neural Tube - Galdo, mark; Fiore, Christelle S.; Gregonis, Jennifer; Compagnone, Nathalie A. (Frontiers in Endocrinology, 2012)
Dehydroepiandrosterone (DHEA) is synthesized from cholesterol by activity of P450scc and P450c17, enzymes that we previously characterized in the developing nervous system. We describe the localization of P450c17 in the differentiated field of the ventral spinal cord in different motor-neuron subtypes. We show that, during organogenesis, P450c17 activity is regulated along the antero/posterior axis of the spinal cord concomitantly with the gradient of neurogenesis. To examine whether DHEA may modulate this process, we measured proliferation and differentiation of ventral neural precursors in primary and explant cultures. Our results showed that DHEA induce the expression of class II protein Nkx6.1, motor-neuron precursor Olig-2, and definitive motor-neuron marker Isl1/2. DHEA also promoted proliferation of ventrally committed precursors in isolated spinal-cord precursor cultures and in whole spinal-cord explants. Both the proliferative and inductive effects of DHEA were dependent on sonic hedgehog signaling. The possibilities that the effects observed with DHEA were due to its metabolism into androgens or to activation of NMDA receptor were excluded. These results support the hypothesis that the tight regulation of DHEA biosynthesis may be a biologic clock restricting the period of ventral neuronal precursor proliferation, thus controlling the number of pre-committed neurons in the developing neural tube.